Persona Used by the Characters in Novel The Balance Project by Susie Orman Schnall - Dewi, Maya Kurnia; Pratama, Mochamad Rizqi Adhi (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
The story of The Balance Project is a novel written by Susie Orman Schnall about the efforts of the characters to show the world about how to balance between work and life because they involve in the industry campaigning the slogan. However in fact, they still struggle to balance it. This novel shows the persona used by the characters to cover their real self to the world. The purpose of this study is to dissect the literary psychology of the characters in the novel The Balance Project by using the persona theory which is one of the four concepts of the structure of the collective unconscious in the human soul which includes persona, anima-animus, shadow, and self. The method used is descriptive qualitative using a literary psychology approach with the persona theory proposed by Carl Jung as a reference. The data collection techniques used are library research techniques and note-taking studies. The results of this study refer to the analysis of persona theory in the novel which includes two sources of persona, persona development, persona transformation, and persona integration process. In order to hide their real self, the characters use persona to show the world that they are good with balancing work and life. The characters use persona because they must meet the expectation from the society and their own ambition. The persona then develop and transform to meet it but eventually they will find the integration of persona and shadow when they have been able to accept themselves over their persona.